Organizational And Methodological Aspects Of Teaching Specialty Modules - Saypillayeva Hilola Barot Qizi (Zien Journals, 2024)
In this article, the modern development of the educational services market, the new rules for the use of technologies in education are explained in more detail. The purpose of the article is to analyze the introduction of innovative educational technologies into the system of training specialists in pedagogy and psychology based on the existing European experience. For its implementation, comparative analysis, concretization and generalization methods were used. They eased the task of describing the main features of the organization of an innovative educational space on the example of the activities of modern universities in the EU countries. In the results, the general principles of changes in the training of specialists in pedagogy and psychology were analyzed, innovative technologies were defined in the modern understanding of their use in personnel training
Keywords: Educational technologies; specialty modules; organizational aspects